The Role of Women in Plant-based Textile Production during the Viking Diaspora in Scotland and the Irish Sea Region. - Freeman, Susan (Scottish Historical Review, 2021)
Evidence for textiles in viking-age Scotland and the adjacent Irish Sea region derives from small fragments usually surviving as mineralised products associated with metal dress fittings and grave goods such as shield bosses and weaving battens, excavated from the furnished graves of both women and men. Since Scottish viking-age textiles were last reviewed over twenty years ago, this paper collates information from antiquarian finds and more recent excavations which employed considerably enhanced techniques for retrieving fragile archaeological textiles. Evidence is presented for the occurrence and role of plant-based textiles derived from flax and hemp including linen in funerary processes as burial garments, shrouds and wrapping other grave goods, such as weapons and tools. Many richly appointed women's graves in viking-age Scotland were accompanied by tool assemblages used in the manufacture and maintenance of textiles. The presence of these tools raises questions about the status of textile production and the roles women played in it.